Perancangan Aplikasi Lirik Kidung Jemaat Dan Chord Untuk Lagu Sekolah Minggu Berbasis Android - Baskoro, Tian; Saian, Pratyaksa Ocsa Nugraha (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Nowadays, society uses a lot of digital and practical services, including church canteens or other spiritual songs such as Kidung Pasamuan Jawi, Pelengkap Kidung Jemaat and others. Because it requires innovation or a change to support a variety of private activities, for example in church services and sunday school songs. The innovation can use smaartphone technology, because it is then made an Android-based application system with the purpose and purpose can produce a smartphone application that can be used and used to help in worship activities. In this study is planned the design of Android application with the help of Android studio and with the aid of firebase as the method of making this application, it is hoped this research can help the devotion in the church who still use the Nyanyian Rohani, such as the Kidung Jemaat, as well as help the youth as a learning and aiding tool in playing music and others